Mineralisasi Emas di gunung Gupit, Magelang, Jawa Tengah: Sebuah Penemuan Baru Prospek Emas Tipe Ephitermal Sulfidasi Tinggi pada Rangkaian Pegunungan Kulon Progo-Menoreh - Idrus, Arifudin; Warmada, I Wayan; Putri, Resty Intan (2013)
Study area covering Guning Gupit and its vicinity, Magelang Regency, Central Java situated in the most northern part of the Kulon progo-Menoreh mountain range hosts a new discovering gold prospect of high sulfidation ephitermal deposit. This paper is aimed to elucidate ore geological aspects controlling the mineralization and some genetic characteristics of the deposit including mineralogy, ore/quartz vein texturesand geochemistry.